Begraafplaatsen en kerkhoven - een stand van zaken (Bulletin KNOB, 2003)
This contribution was presented at the KNOB workshop Funerary Heritage on 11 April 2002 in the Pieterskerk in Utrecht. The purpose of the workshop was to inform those present of the state of affairs as regards the inventory and protection of cemeteries (including the churchyards).A cemetery - even a protected one - is to be regarded as an enterprise that should be able to function efficiently and, if possible, be financially sound. A purely cultural-historical approach is not sufficient. On the basis of a number of existing cases a Plan for Conservation and Development was made in such a way that it is generally applicable.In order to see to it that the Jewish cemetery on Scheveningseweg in The Hague retains its distinctive character as much as possible, the starting point 'attendant decline' was introduced. In addition, a framework and policy are being developed besides a funerary heritage data base, set up in 1998 by co-operation between De Terebinth and the Netherlands Department for Conservation (RDMZ (RCE)).Thanks to the MIP/MSP a large number of cemeteries dating from the period 1850-1940 were protected by the government and thus in a certain sense secured. Nevertheless, it appears that some managers do not even know that their cemetery is protected.By means of pilot projects it should be investigated these coming years how this policy is to be realised as regards contents as well as from the point of view of conservation. Regular evaluation and cooperation with all the authorities involved is a precondition in all of this.